HYDROCHEMICAL AND ISOTOPIC BEHAVIOUR OF A SAHARAN PHREATIC AQUIFER SUFFERING SEVERE NATURAL AND ANTHROPIC CONSTRAINTS (CASE OF OUED-SOUF REGION, ALGERIA) - Guendouz A.; Moulla A.S.; Remini B.; Michelot J.L. (My University, 2006)
An approach combining the use of water dissolved chemical species and isotopic fingerprints has been used to understand the behavior of a phreatic aquifer and to determine the origin of its different water components. This aquifer is located in the large sedimentary basin of the Great Oriental Erg (Algeria) and overlies two deeper aquifers: the Complexe Terminal (CT) and the Continental Intercalaire (CI). Besides the deterioration of its groundwater quality, its water table has risen during the last 20 years. A water budget surplus between 950 and 2500 l s−1 was estimated. Down-gradient groundwater evolution (south-north) has shown that the mineralisation increases from 1.23 to 5.20 g l−1 due to evaporite minerals dissolution. Chemical and isotopic data demonstrated that in addition to rainfall there is a contribution from the CT and CI aquifers. The latter are tritium-free and less mineralized than the phreatic aquifer. Their radiocarbon contents are very low (<10 pmC, percent modern Carbon) (Pleistocene recharge) whereas quite the contrary is observed for the superficial aquifer which exhibits fairly high and variable C-14 activities (50–100 pmC), evidence of recent recharge. On the basis of tritium contents, two groundwater groups were identified for the phreatic aquifer.
Keywords: HYDROCHEMISTRY; STABLE ISOTOPES; RADIOISOTOPES; SAHARA; ALGERIA; Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен